The Holodomor in Ukrainian Literature - Gaidash, Anna (Studia Philologica, 2025)
This lecture, delivered on July 3, 2025, at Ludwig Maximilian University of Munich within the workshop “Counter-Sentences. Feminist Perspectives in Slavic Studies”, forms part of the broader project “The Memory of the Holodomor in Slavic Literature” (Leipzig University, 2024). The project aims to introduce Western academia to the diverse literary and cultural representations of the Holodomor across various genres, including prose, drama, poetry, comics, and film. The lecture begins with an overview of Ukrainian literature and its role in shaping Holodomor Studies, followed by a discussion of current scholarly approaches to interpreting famine narratives. It then explores the representation of the Holodomor in fiction written both in emigration and in Ukraine itself. Finally, the lecture presents two case studies: Vasyl Barka’s Der gelbe Fürst (1962), a canonical novel about Holodomor written in immigration, and Tanya Pyankova’s Das Zeitalter der roten Ameisen (2022), a contemporary engagement with the famine’s memory written in independent Ukraine. Together, these perspectives highlight how literature negotiates trauma, memory, and identity in relation to one of the twentieth century’s most devastating historical events.